INTERACTS (INTErventional Radiotherapy ACtive Teaching School) guidelines for quality assurance in choroidal melanoma interventional radiotherapy (brachytherapy) procedures - Tagliaferri, Luca; Pagliara, Monica Maria; Boldrini, Luca; Caputo, Carmela Grazia; Azario, Luigi; Campitelli, Maura; Gambacorta, Maria; Smaniotto, Daniela; Frascino, Vincenzo; Deodato, Francesco; Morganti, Alessio Giuseppe; Kovács, György; et al. (Journal of Contemporary Brachytherapy, 2017)
Eye plaque brachytherapy represents a safe and effective therapeutic approach for choroidal melanoma, combining clinical outcomes with an eye and visual preservation. As it represents a complex procedure, a specific quality assurance program is strongly suggested to improve patients and operators safety, and to reduce possible complications linked to surgical procedure and radiation exposure. The aim of this paper is to describe the INTERACTS (Interventional Radiotherapy Active Teaching School) guidelines for quality assurance in choroidal melanoma interventional radiotherapy (brachytherapy) used in our institution.